Chronic obstructive pulmonary disease mortality trends in Spain, 1980-2020 - Lucia Cayuela; José Luis López-Campos; Anna Michela Gaeta; Rocio Reinoso-Arija; Aurelio Cayuela (Epidemiology and Health, 2023)
OBJECTIVES In Spain, there has been a recent increase in the mortality rate for chronic obstructive pulmonary disease (COPD) in younger women. This study aimed to analyze trends in the COPD mortality rate in Spain from 1980 to 2020, evaluating any differences between genders and age groups. METHODS Death certificates and mid-year population data were obtained from the Spanish National Institute of Statistics. For both genders, age group-specific and standardized (overall and truncated) rates were calculated by the direct method using the world standard population. The data were analyzed using the joinpoint regression method. RESULTS In both men and women, the number of COPD deaths increased from 1980 to 1999 (average annual increase of 7% in men and 4% in women), while from 1999 onwards, deaths decreased by -1.0% per year in both genders. In women, there was a significant final period of increase in the 55-59 to 70-74 age groups and a slowing of the decline in the over 75 age group. Additionally, an increase in mortality for the truncated rates was observed for women between 2006 and 2020. In men under 70 years of age, there was an initial period in which death rates remained stable or significantly increased, followed by a period in which they decreased significantly. CONCLUSIONS Our study shows age and gender differences in COPD mortality trends in Spain. Although the data show a downward trend, we have identified a worrying increase in the truncated rates in women for the last few years.